La voz de los actores en los aniegos de San Juan de Lurigancho, Lima, año 2019: un análisis comparativo de los discursos social, mediático y político - Salazar Melgar, Raul Orestes (2020)
The general objective of this research is to analyze, in a comparative way, the social, media and political discourse, regarding the floods of San Juan de Lurigancho - Lima, year 2019, from an approach to the voice of the actors involved. The methodology was developed under the principles and guidelines of qualitative methodology, based on the design of critical discourse analysis that is assumed from the Norman Fairclough approach. The sample consisted of 10 social actors and one political, a representative of Sedapal; likewise, a documentary review was made. The results indicated that the discourses between social, political and media actors diverge in reference to the person responsible for the damage and converge on how devastating the phenomenon was. In addition, they demonstrate that it is necessary to seek strategies to prevent an event of this magnitude in the future.